PERMANENT EDUCATION IN HEALTH AND KNOWLEDGE MANAGEMENT: INITIATIVES IN THE REGIONAL HEALTH SUPERINTENDENCE - Daniele Knopp Ribeiro; Denise Barbosa de Castro Friedrich (Universidade Federal do Paraná, 2023)
Objective: to provide the Permanent Education in Health and Knowledge Management actions carried out at the Regional Health Superintendence of Minas Gerais - Brazil, and to reflect on the possible parallels. Method: this is a qualitative and exploratory study conducted with 10 health workers. Data collection took place from February to May 2021 using a remote instrument prepared via Google Forms, and analyzed according to Bardin's Thematic Content Analysis technique. Results: there are formal and informal training and knowledge sharing processes, construction and transformation of work processes, as well as fragmentation, sectorization and competitiveness based on information. Conclusion: the results have the potential to stimulate discussion about the various knowledge movements in the health regions, attentive to the elaboration and implementation of state and regional Permanent Health Education and Knowledge Management plans conceptually aligned and committed to the territory.